2015
DOI: 10.1212/wnl.0000000000001329
|View full text |Cite
|
Sign up to set email alerts
|

Autologous hematopoietic stem cell transplantation in multiple sclerosis

Abstract: Intense immunosuppression followed by AHSCT is significantly superior to MTX in reducing MRI activity in severe cases of MS. These results strongly support further phase III studies with primary clinical endpoints. The study was registered as EUDRACT No. 2007-000064-24.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
179
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(190 citation statements)
references
References 38 publications
2
179
1
8
Order By: Relevance
“…Early adverse events were considered as expected and occurred at least in 80% of treated cases. SAE occurred in the aHSCT arm only and resolved without sequelae [31]. Despite these encouraging results, and improvement of clinical expertise, this type of treatment need to be performed only in selected centers with known neurological and hematological expertise.…”
Section: Treatment Choices: Past and Present Experiencesmentioning
confidence: 99%
“…Early adverse events were considered as expected and occurred at least in 80% of treated cases. SAE occurred in the aHSCT arm only and resolved without sequelae [31]. Despite these encouraging results, and improvement of clinical expertise, this type of treatment need to be performed only in selected centers with known neurological and hematological expertise.…”
Section: Treatment Choices: Past and Present Experiencesmentioning
confidence: 99%
“…It was also reported that patients with Gd-enhancing activity at baseline fared significantly better than patients without Gd-enhancing lesions 1,33 , pointing out that the clinical effect of aHSCT is mainly due to the capacity to suppress the inflammatory activity. Recently, a series of papers has unequivocally demonstrated the effect of aHSCT on MRI signs of activity and on the clinical outcome in severe forms of MS. A comparative randomized phase II trial evaluating aHSCT vs mitoxantrone -the ASTIMS trial-demonstrated that the number of new T2 lesions in a 4 year period was decreased of 79% in patients treated with aHSCT vs the cases that received mitoxantrone 7 . In the observational study reporting the Swedish experience 1 and in the prospective HALT study in USA 4,5 , patients with a RR form of the disease who experienced relapses and progression of the disease before treatment were followed for a median follow up of 5 years, demonstrating a sustained remission of disease without progression of disability in 77% and 80% of cases respectively.…”
Section: The Second Period From 2005 To 2017mentioning
confidence: 99%
“…One would probably not opt for fingolimod in that situation if the expected disease activity is very high despite very effective therapy. A few centers offer autologous stem cell transplantation in such a situation [97], but this approach is still in development and safety and efficacy still have to be assessed in larger cohorts. Breakthrough disease is, however, not the only reason for a need to switch therapies.…”
Section: Switching Between Second-line Therapiesmentioning
confidence: 99%